Separation of organophosphorus pesticides using micellar electrokinetic chromatography - W. Ibrahim, W. Aini; Monjurul Alam, S. M.; Sulaiman, Azli (Penerbit UTM Press, 2003)
Separation of six organophosphorus pesticides (mevinphos, methidathion, diazinon, profenofos, quinalphos and chlorpyrifos) has been investigated using micellar electrokinetic chromatography (MEKC) with on-column UV-Vis detection. Separations involved using anionic sodium dodecyl sulphate (SDS) surfactant and phosphate or borate buffer as carrier electrolytes. Separations have been found incomplete regardless of changing all sort of possible factors such as buffer types, buffer and surfactant concentrations, addition of organic modifier, methanol and pH of the running buffer. Irrespective of the combinations of levels of factors, mevinphos alone appeared always as a distinguishable strong peak followed by diazinon and methidathion. Even in the absence of any surfactant in buffer matrices, mevinphos and diazinon were detected but methidathion, profenofos, quinalphos and chlorpyrifos were undetected. The use of 6 mM b-cyclodextrin (Ã¢ CD), 20 mM borate buffer with 40 mM SDS and buffer pH of 9.5 resulted in the best separation of mevinphos, diazinon and methidathion. The results found in this study might reflect the solubility and hydrophobicity properties of the pesticides.